Evaluating correlations between reading ability and psychophysical measurements of dynamic visual information processing in Japanese adults - Ryohei Nakayama; Miki Uetsuki; Kazushi Maruya; Hiromasa Takemura (Scientific Reports)
Abstract The reading ability of English readers has been shown to correlate with psychophysical measurements of dynamic visual information processing. This study investigated the relationship between reading ability and dynamic visual information processing in healthy adult native Japanese readers (n = 46). Reading ability was assessed using three different tests: the Japanese Adult Reading Test (JART), transposed-letter detection task, and oral reading. Principal component analysis was performed on the scores on the three reading tests to quantify reading ability. Psychophysical thresholds were measured for contrast detection and speed discrimination with a drifting grating stimulus as well as for tracking two targets among concentrically revolving objects, providing an upper speed limit for attentional tracking. Simple correlation analysis revealed that one of the principal components correlated with the tracking speed limit. In addition, another principal component correlated with the speed-discrimination threshold, which is consistent with previous findings in English readers. These results suggest that Japanese reading ability involves at least two different processes, each sharing underlying mechanisms with visual motion and attentional processing.